(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The brand is an important element of creating the image and positioning of Poczta Polska and Deutsche Post in the market. The aim of this article is to compare the opinions of selected courier companies in the assessment of customers in Poland and Germany and to compare their image in the customer’s opinion. The following research methods were used: literature analysis, comparative analysis and indirect survey method using questionnaire survey technique. Brand awareness is increasing and is noticeable in the form of rebranding the Polish Post. Attempts taken to position their offer may decide the competitive advantage of the described companies on the Polish and German markets.